2019
DOI: 10.1088/1361-665x/ab0b8e
|View full text |Cite
|
Sign up to set email alerts
|

Structured magnetic circuit for magnetorheological damper made by selective laser melting technology

Abstract: Eddy currents are the main reason causing for the long response time of a magnetorheological (MR) damper. Eddy currents are often unwanted parasitic phenomenon for many electromagnetic machines working with an alternating magnetic field. Their reduction can be secured by the use of material with high electrical resistivity such as ferrites or soft magnetic composites. These materials, however, exhibit bad mechanical properties and cannot be used in mechanically loaded parts. Eddy currents can also be reduced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…However, the primary response time for control current drop is independent of piston velocity. It is noteworthy that similar trends were experimentally determined in other research studies [42,43].…”
Section: Influence Of Electric Conductivitysupporting
confidence: 89%
“…However, the primary response time for control current drop is independent of piston velocity. It is noteworthy that similar trends were experimentally determined in other research studies [42,43].…”
Section: Influence Of Electric Conductivitysupporting
confidence: 89%
“…The cohesion of chain formations causes an increase in the apparent viscosity of MR fluid [ 2 ]. This property is most often exploited by MR dampers [ 3 , 4 , 5 ], brakes/clutches [ 6 , 7 , 8 ], seals [ 9 , 10 ], or flexible structures [ 11 , 12 ]. The applicability of these MR devices in smart mechanical systems has several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The change of apparent viscosity is caused by particles aligning in the direction of the magnetic field. Several designs of the MR damper can be found that differ in the number of coils [2,3,4] , the arrangement of the magnetic circuit [3,4,5] and the number of gaps [6,7] etc. If the power supply of the electromagnetic coil is interrupted during damper operation, the damper will remain at the minimum damping level.…”
Section: Introductionmentioning
confidence: 99%
“…Strecker et al [17] and Kubík et al [4] published the design of the MR damper with a short response time in which the ferrite material of the magnetic circuit was used. Strecker et al [5] published an MR damper with a magnetic circuit manufactured by 3D metal printing. This design method provides a MR damper with a short response time of 1.68 ms and a high dynamic force range.…”
Section: Introductionmentioning
confidence: 99%